Intervention model for exposure and control of biological risk. Study of universal precautions in nursing staff - Jaimes Delgado, Pedro Emilio; Pérez Olmos, Liliana Margarita; Celis Salazar, Orlando (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
In recent years, analyzes were carried out in hospitals in Colombia that showed that there were patients who contracted dangerous bacteria during their stay in some health institutions. In addition to patients, all health personnel are exposed to these pathogens, as they are present in the environment. They are threats of natural origin that extend beyond private spaces and activities of people, and that due to their magnitude, speed and contingency require a management process in which better and greater control is required to mitigate the risk. resulting effect.